The chemical redox modulated switch-on fluorescence of carbon dots for probing alkaline phosphatase and its application in an immunoassay. Issue 1 (20th December 2017) - Song, Pei; Liu, Qian; Zhang, Ying; Liu, Wei; Meng, Meng; Yin, Yongmei; Xi, Rimo
Abstract : The chemical redox modulated switch-on fluorescence of carbon dots for detecting ALP and human IgG. Abstract : Early diagnosis is an important requirement for the early treatment of diseases and reliable detection methods for biomarkers are indispensable tools for early diagnosis. However, recent innovations in analytical technology are rarely employed widely due to multiple factors including the requirement of specialized equipment and infrastructures. Hence, much attention has been focused on exploring universal nanoprobes for routine practices. Here, we report a chemical redox modulated switch-on fluorescence strategy based on versatile carbon dots (CDs) for probing alkaline phosphatase (ALP) and human IgG (a model target). The fluorescence of the CDs is initially quenched by Fe(iii ) and then restored by ascorbic acid, which is generated from the hydrolysis of ascorbic acid 2-phosphate (AAP) by the catalysis of ALP. Based on that, a simple "switch-on" fluorescence assay for ALP was designed and leads to a sensitivity of as low as 0.8 U L −1 . The proposed assay is applied in ALP sensing in human serum samples. Additionally, the application of the switch-on fluorescence strategy is successfully expanded to the immunoassay of human IgG in serum from healthy adults and patients with systemic lupus erythematosus. The developed sensing system could be devised for various target sensors and has promising potential in the field of biological analysis and clinical diagnostics.